Trust and trustworthy computing 4th international conference, TRUST 2011, Pittsburgh, PA, USA, June 22-24, 2011 : proceedings - TRUST (Conference) Vienna, Austria) 2012; McCune, Jonathan M; SpringerLink (Online service). (New York Springer, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Trust and Trustworthy Computing, TRUST 2011, held in Pittsburgh, PA, USA in June 2011. The 23 revised full papers presented were carefully reviewed and selected for inclusion in the book. The papers are organized in technical sessions on cloud and virtualization, physically unclonable functions, mobile device security, socio-economic aspects of trust, hardware trust, access control, privacy, trust aspects of routing, and cryptophysical protocols.
Electronic reproduction.
Keywords: Computer security -- Congresses; Internet -- Security measures -- Congresses; Electronic books